2017
DOI: 10.1002/2016gc006550
|View full text |Cite
|
Sign up to set email alerts
|

Rapid variations in fluid chemistry constrain hydrothermal phase separation at the Main Endeavour Field

Abstract: Previous work at the Main Endeavour Field (MEF) has shown that chloride concentration in high‐temperature vent fluids has not exceeded 510 mmol/kg (94% of seawater), which is consistent with brine condensation and loss at depth, followed by upward flow of a vapor phase toward the seafloor. Magmatic and seismic events have been shown to affect fluid temperature and composition and these effects help narrow the possibilities for sub‐surface processes. However, chloride‐temperature data alone are insufficient to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…The estimated heat flux for the entirety of the active Endeavour hydrothermal fields is ∼800 MW with a mean temperature of ∼300°C (Kellogg, 2011). The concentration of CO 2 within the vent fluids for periods not impacted by dike emplacements is on the order of 15–20 mmol/kg, with 80% of the output believed to be sourced from melt (Love et al., 2017; Proskurowski et al., 2004). Taking a change in enthalpy of 1,600 kJ kg −1 between 0 and 350°C at 220 bars for a 3.2 wt.% NaCl solution (Anderko & Pitzer, 1993), we estimate that the VFs emit 10,000–14,000 tons of melt‐derived CO 2 per year.…”
Section: Discussionmentioning
confidence: 99%
“…The estimated heat flux for the entirety of the active Endeavour hydrothermal fields is ∼800 MW with a mean temperature of ∼300°C (Kellogg, 2011). The concentration of CO 2 within the vent fluids for periods not impacted by dike emplacements is on the order of 15–20 mmol/kg, with 80% of the output believed to be sourced from melt (Love et al., 2017; Proskurowski et al., 2004). Taking a change in enthalpy of 1,600 kJ kg −1 between 0 and 350°C at 220 bars for a 3.2 wt.% NaCl solution (Anderko & Pitzer, 1993), we estimate that the VFs emit 10,000–14,000 tons of melt‐derived CO 2 per year.…”
Section: Discussionmentioning
confidence: 99%
“…Pronounced changes in seismic activity, permeability, heat flux, temperature and vent fluid chemistry result from intermittent dyking and volcanic eruptive or tectonic events at MORs 40,86,108,110 . Large increases in CO 2 could precede volcanic events, as documented at the Main Endeavour Field following an earthquake swarm in 1999 40,111,112 . Lava interacting with hydrothermal circulation cells produces extreme changes in water-rock reactions and the nature and degree of phase separation.…”
Section: Impact Of Magmatic Eventsmentioning
confidence: 98%
“…In these same settings, Coogan et al (2017) revealed insights about near-vent chemical processes in plume while Jackson et al (2017) described diffuse hydrothermal flow using sound. Love et al (2017) showed that there were variations in fluid chemistry that constrained hydrothermal vent phase separation. In 2017, Xu published three studies with co-authors that show the impact of tides on hydrothermal vents, further advancing the quantification of hydrothermal venting, and advanced the techniques in using acoustic imaging to study venting (Xu et al, 2017a,b,c).…”
Section: Seafloor Ocean and Atmospheric Linksmentioning
confidence: 99%